(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
Today the right to decent and decent housing is presented as an extremely important constitutional right for the citizen, given that he needs a habitat to live in, that is, a space where his life unfolds and lives in a safe environment. And pleasant. So, to speak of quality and consolidated housing, what is known as community quality is needed, which is defined as an indicator to measure the quality of the right to housing, however, this is seen affected by community conflicts that occur throughout the habitat, which is a challenge for alternative dispute resolution mechanisms, such as community mediation, whose mission is to ensure the community quality of the people who live in a community. certain neighborhood or city.